Selective degradation of acetaminophen from hydrolyzed urine by peroxymonosulfate alone: performances and mechanisms. Issue 63 (16th December 2021) - Lin, Yiting; Mo, Xiting; Zhang, Yamin; Nie, Minghua; Yan, Caixia; Wu, Leliang
Abstract : Owing to the high concentration of pharmaceuticals in urine, the degradation of these organic pollutants before their environmental release is highly desired. Abstract : Owing to the high concentration of pharmaceuticals in urine, the degradation of these organic pollutants before their environmental release is highly desired. Peroxymonosulfate (PMS) is a desirable oxidant that can be applied to environmental remediation; however, the performance and mechanism of PMS for the degradation of pharmaceuticals in the urine matrix have not been investigated. Herein, PMS was first discovered to efficiently degrade typical pharmaceuticals in hydrolyzed urine (HU) by selecting acetaminophen (ACE) as a target compound. Quenching experiments revealed that singlet oxygen ( 1 O2 ) and hydroxyl radicals (HO˙) were observed in the HU/PMS system, but the principal reactive species (RS) responsible for ACE removal was 1 O2 . The major constituents of HU, including SO4 2− and organics (creatine, creatinine and hippuric acid), hardly affected the elimination of ACE, whereas Cl −, H2 PO4 − and NH4 + would accelerate ACE degradation. Besides, HCO3 − slightly inhibited this process. The ACE degradation efficiency was enhanced using photo-irradiation, including sunlight and visible light, although increasing the reaction temperature could, interestingly, hardly accelerate the degradation rate of ACE. Three-dimensional excitation–emission matrices (3D-EEMs) have indicated that other intermediates that have a higher fluorescence intensity might be generated in the HU/PMS system. Finally, nine intermediate products were determined and the degradation pathways of ACE were proposed. Overall, the results of this study illustrated that PMS is an efficient oxidant for the degradation of ACE in HU.